1975
DOI: 10.1111/j.1528-1157.1975.tb04726.x
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy and Pregnancy: A Study of 153 Pregnancies in 59 Patients

Abstract: The relation of epilepsy with gestation was studied in 59 patients through 153 pregnancies. In patients with idiopathic epilepsy, 45 per cent had more frequent fits during pregnancy, 50 per cent were unchanged, and 5 per cent were improved. The results in patients with symptomatic epilepsy were similar. Patients with a high frequency of fits in the pregestational state are likely to have an increased number when pregnant. Two cases of status epilepticus were treated successfully without interruption of pregnan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
89
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(98 citation statements)
references
References 17 publications
4
89
1
Order By: Relevance
“…I and II of Obstetrics and Gynecology, University of Helsinki, Finland An increased rate of malformations, particularly oral clefts, of newborn infants born to epileptic mothers has been reported in several studies [1,2,3,4,7]. Although maternal Ingestion of antiepileptic drugs is strongly suspected of causing congenital defects, the effect of epilepsy itself or a combined effect of drug intake and epilepsy have not been excluded äs etiological factors.…”
mentioning
confidence: 99%
“…I and II of Obstetrics and Gynecology, University of Helsinki, Finland An increased rate of malformations, particularly oral clefts, of newborn infants born to epileptic mothers has been reported in several studies [1,2,3,4,7]. Although maternal Ingestion of antiepileptic drugs is strongly suspected of causing congenital defects, the effect of epilepsy itself or a combined effect of drug intake and epilepsy have not been excluded äs etiological factors.…”
mentioning
confidence: 99%
“…[24] Nevertheless, several other studies have not demonstrated an excess risk of abortion in WWE. [14,25,26] There are conflicting reports regarding the in creased risk of nonpreteinuric hypertension, [27] pre-eclampsia, eclampsia, and abruptio placenta in WWE. Frequency of cesarean section may be increased for WWE, although most of them can have normal vaginal delivery.…”
Section: Effect Of Epilepsy On Pregnancy Infertilitymentioning
confidence: 99%
“…Seizure frequency may remain unchanged or decreases in two-third of WWE, whereas it may increase in others. [14] Seizure frequency may also vary between pregnancies in the same woman. There can be diverse patterns of seizure frequency during pregnancy.…”
Section: Effect Of Pregnancy On Epilepsymentioning
confidence: 99%
“…[2][3][4] A few studies have focused on the effect of pregnancy on epilepsy and a possible worsening of epilepsy during pregnancy, but there are studies which do not show increase in seizure frequency during pregnancy and puerperium. [5][6][7] About 2.5 million women in India suffer from epilepsy, with 52 (25%) of them being in the reproductive age group. 8 Majority of women with epilepsy will have normal, healthy infants.…”
Section: Introductionmentioning
confidence: 99%